New Economic Geography - Hans-Friedrich Eckey; Reinhold Kosfeld (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2004)
The standard model of New Economic Geography (NEG) presents a synthesis of polarization and neo-classical theories. Within a monopolistic competition framework it aims to explain processes of concentration and deconcentration of manufacturing in a two-sector economy. In this paper the effects of several assumptions of spatial agglomeration processes are addressed. In particular, we investigate the effects of transport costs for agricultural goods, spatial spillovers, the presence of non-tradable services and limited mobility of the labour force. It becomes clear that the tendency towards deconcentration of manufacturing is more marked the higher the transport costs for agricultural goods, the stronger the positive spillovers across the regions, the more income spent on services, the more limited the mobility of the labour force. – – Das Grundmodell der NÖG stellt eine Synthese zwischen der Polarisationstheorie und der Neoklassik dar. In methodisch sehr anspruchsvoller Weise werden (De-) Konzentrationstendenzen der Industrieproduktion erklärt. Hierbei werden jedoch eine Reihe von einschränkenden Annahmen getroffen, die in Widerspruch zur Realität stehen. In diesem Beitrag werden einige von ihnen aufgehoben und ihre Auswirkungen auf räumliche Agglomerationsprozesse untersucht. Im Einzelnen handelt es sich um Transportkosten für Agrargüter, räumliche Überschwappeffekte, die Existenz von nicht handelbaren Dienstleistungen und eine eingeschränkte Mobilität der Arbeitskräfte. Dabei zeigt sich, dass eine Tendenz zur Dekonzentration der Produktion umso ausgeprägter ist, je höher die Transportkosten für Agrargüter sind, je mehr positive Spillovers zwischen den Regionen vorhanden sind, je stärker das Einkommen zum Kauf von Dienstleistungen verwendet wird, je eingeschränkter die räumliche Mobilität der Arbeitskräfte ist.
Keywords: R10; R12; 330; Neue Ökonomische Geographie; Transportkosten; nicht handelbare Dienstleistungen; Spillovers; New Economic Geography; transport costs; non-tradable services; spillovers; Neue ökonomische Geographie; Transportkosten; Spillover-Effekt; Nicht-handelbares Gut; Theorie